Analisis Tingkat Pengetahuan Masyarakat Dalam Penanggulangan Dampak Kesehatan Akibat Bencana Banjir di Desa Pone Kecamatan Limboto Barat Kabupaten Gorontalo - Pipin Yunus; Sabirin B Syukur (Kampurui Jurnal Kesehatan Masyarakat, 2021)
Disasters are events that threaten people's lives that can occur anytime and anywhere, which can be caused by natural factors or non-natural factors (human factors) that they can cause environmental damage, loss of property, psychological impacts and even fatalities. types of disasters include  flood. The purpose of this study was to determine the level of community knowledge in dealing with health impacts due to flooding in Pone Village, Limboto Barat District. This research applied quantitative descriptive  which aims to describe the variables in the study. The samples are 60 people with purposive sampling technique. The results showed that the level of community knowledge in dealing with health impacts due to flooding was included  in the lack category are  22 respondents and included in the level of knowledge in  good category as many as 38 respondents. In conclusion, Public knowledge in flood disaster management is still categorized as low.